The Prevalence And Associated Factors Of Denture Wearing Associated Oral Lesions Among Dental Patients Attending College Of Dentistry Clinics In Aljouf University - Zwiri, Abdalwhab M. A. (European Scientific Journal, ESJ, 2016)
Background: oral lesions can be induced by wearing dentures and have been associated with impacting the quality of life of dental patients. Study objectives: to determine the prevalence of denture associated oral lesions and their associated possible factors in college of dentistry clinics, Aljouf University. Methods and subjects: this was a retrospective study to collect data from files of patients who wear dentures. The study included 344 patients. All files were reviewed and the extracted data were further analyzed using SPSS version 20. The relationships between variables were tested using One Way Anova and Pearson correlation. Data were presented as frequencies, percentages, means, and standard deviation. Significance was examined at alpha < 0.05. Results: a total of 344 files were reviewed. The following oral lesions were found: denture stomatitis (48.8%), papillary hyperplasia (39.8%), traumatic keratosis (22.1%), angular cheilitis (16.9%), and erythematous candidiasis (10.2%). No significant relationships were found between oral lesions and both age and gender bases on One Way Anova test. Pearson correlation showed a significant positive correlation between traumatic keratosis and age (r=0.110, p=0.042), and a negative correlation between traumatic keratosis and erythematous candidiasis (r=-0.110, p=0.039). Conclusions: The present studies showed that oral lesions associated with wearing denture are prevalent and create health problems that impact the quality of life of dental patients